Determination of the physicochemical indexes of Rosmarinus officinalis, Cymbopogon citratus and Cymbopogon winterianus essential oils (Research, Society and Development, 2020)
The quality control in essential oils is of great importance to avoid adulteration of these products, however there is little information about the physical and chemical characteristics. In this way, the objective of this work was to perform physical-chemical analysis of three essential oils samples of Rosmarinus officinalis, Cymbopogon citratus and Cymbopogon winterianus. The essential oils were obtained from two commercial suppliers and coded as Comercial 1 and 2. These oils were compared with oils extracted by hydrodistillation from leaves of plants implanted in the Medical Garden of the University and codified as Cultivated. The essential oils were obtained by hydrodistillation for 3 hours for R. officinalis and 2 hours for C. citratus and C. winterianus. The absolute density (g/mL), refractive index and the chemical composition (GC / MS) of the oils were determined. For the density and the refractive index, the results indicated that there were no differences between the commercial and cultivated samples, however, in the chemical composition, differences were observed among the major compounds. For rosemary oil, 1.8-cineole stood out with 5.82% (Cultivated), 17.28% (Commercial 1) and 27.42% (Commercial 2). For lemongrass essential oil, myrcene has 8.52% (Cultivated) and the absence of those from both commercial suppliers. For citronella essential oil, limonene was found at 9.55% (Commercial 2), 2.31% (Commercial 1), and 3.62% (Cultivated), indicating that the variation in the percentage of compounds may have been caused by abiotic and biotics factors, as the samples come from cultures implanted in different locations, interfering in the characteristics of these essential oils.